Photographic study of eclipsing binaries IY Aur, RX Ari, DG Per, ZZ Cnc - Antonyuk, K. A. (Одеські астрономічні публікації, 2017)
Photometric elements for four stars, brightness of the comparison stars and moments of 67 weakenings are determined.